Non-occupational but work-related diseases - Legislation, judicature and potential implications to employers and employees in Poland - Andrzej Marcinkiewicz; Paulina Tomczak; Marta Wiszniewska; Jolanta Walusiak-Skorupa; Dominika Dorre-Kolasa (Nofer Institute of Occupational Medicine, 2018)
Background Non-occupational work-related diseases refer to health problems of multifactorial etiology, the occurrence, development and prognosis of which may be affected by work environment or by the way the work is performed but are not treated as occupational diseases under the applicable law. When analyzing their impact on labor market, it is necessary to also consider the employees' right to put in a claim for compensation due to the consequences of the occurrence of such diseases. Material and Methods Legal regulations as well as judicial decisions on the possibilities and methods of pursuing claims for compensation from an employer due to the occurrence of non-occupational work-related disease were analyzed. Results The analyzed legal regulations and judicial decisions referred to the regulations of the Labour Code, Civil Code and Resolution of the Supreme Court of 4 December 1987. The paper presents examples of non-occupational diseases considered to be work-related and conditions necessary to assert a claim by the employee at the court. Conclusions Despite the lack of precise legal regulations in Poland, non-occupational work-related diseases may impact the legal situation of employees as well as employers. Employees are granted the right to claim for compensation from their employers in accordance with the Civil Code. Depending on the employer's legal responsibility, it is necessary to prove the meeting of the appropriate essential conditions to put in a claim for damage. Raising the employers' awareness of the legal and financial consequences shall support the occupational medicine services in intensifying their activity aimed at preventing all work-related diseases. Med Pr 2018;69(5):539-546